Measurement of Low-level radiofrequency electromagnetic fields in the human environment - Misek J; Laukova T; Kohan M; Veternik M; Jakusova V; Jakus J (Acta Medica Martiniana, 2018)
In recent years there has been an increase in development of electromagnetic (EM) technology in the telecommunication industry, resulting in an increase in human non-ionizing exposure. This fact has initiated a number of scientific studies on possible health effects of EM fields on human organism. Totally four representative microenvironments were investigated for RF EM fields distribution, namely: city center, residential area, rural area, and extra-village area. Each microenvironment was measured 20 times in accordance with the International Commission for Non-Ionizing Radiation Protection (ICNIRP) guidelines. The extra-village measurements were taken as the base values that reflect the E-field intensities with the lowest amplitudes. The statistical analysis revealed notable statistical significance (p < 0.001) in almost all measured frequency bands except the Wi-Fi where the p-values were less than 0.05 for the city center and residential area but not significant for rural area. The highest total E-field intensity was measured in the residential area (approximately 1.85 V/m). All measured values were below the legal limits of the Slovak Republic and ICNIRP safety guidelines. However, the ICNIRP safety limits were written in 1998 considering only the thermal effects of RF radiation. They were updated in 2009 without any changes in the limits and still recommend 27.5 – 61 V/m (2 – 10 W/m2) for the RF frequency band of 400–2,000 MHz. The BioInitiative Report of 2012 established the scientific benchmark for possible health risks as 30–60 μW/m2 (approximately 0.1 – 0.15 V/m). Thus, all measured values were above the scientifically derived limits.